Lytic regulated cell death in aquaculture fish - Xiaojing Xia; Bin He; Xiulin Zhang; Zhe Cheng; Mingcheng Liu; Xiaobing Wei; Jinqing Jiang; Jianhe Hu (Reviews in Aquaculture, 2021)
Cell death is an important physiological and pathological phenomenon in multicellular animals and occurs widely in various body’s systems. In recent years, researchers have gained a deeper understanding of the mechanisms of necrosis and apoptosis in mammals. In addition, many new forms of lytic regulated cell death (RCD), such as pyroptosis, necroptosis and ferroptosis, have been discovered, thus enhancing our understanding of the molecular mechanisms of programmed cell death (PCD) and the associated signalling pathways as well as their relationship with diseases. However, our understanding of lytic RCD in fish is limited. Recently, some progress has been made regarding the induction conditions, expression of related genes and regulation of lytic RCD in fish. Furthermore, research on the roles of lytic RCD in tissue development, against pathogenic microorganism, inflammatory disease and neurological disease, has also been advanced. Understanding lytic RCD in fish will enable the regulation of its occurrence through human intervention to inhibit disease processes, improve fish health and explore possible countermeasures based on these basic theoretical studies.